Application of Initial Knowledge to Sentence Structure Writing Competency and Reading Comprehension of Grade VIII Students of SMPN 3 Satu Atap Salapian in 2024/2025 - Gunawan, Hendra; Sutikno, Sutikno; Kartolo, Rahmat; Sari, Erlinda Nofa (Journal of English Language and Education, 2025)
The problem in this research is whether there is an influence of the development of prior knowledge on the ability to create sentence structures and read comprehension of class VIII students at SMP Negeri 3 Satu Roof Salapian, Langkat Regency, for the 2024-2025 academic year. The aim of this research is to determine the effect of developing prior knowledge on the ability to create sentence structures and reading comprehension of class VIII students at SMP Negeri 3 Satu Atap Salapian, Langkat Regency, academic year 2024-2025. The method applied in this research is an experimental method with a simple 2. The instrument used to collect research data is an objective test. An objective test was used to obtain the data needed in this research, which consisted of 20 multiple choice questions, with research techniques, if 1 was correct, it was given a score of 5, so that the highest score was 100 and the lowest score was 5. The results of the research showed that there was an influence on the development of initial knowledge on the ability to create sentence structures and read comprehension for class VIII students at SMP Negeri 3 Satu Roof Salapian Langkat Regency for the 2024-2025 academic year, this can be seen from the results of calculations using anava where Fcount = 6.32 and Ftable = 4.00 at a significance level of 0. .05, this means that Fcount Ftable. Thus, the hypothesis is accepted, meaning that there is an influence of the development of prior knowledge in influencing the ability to create sentence structures and students' reading comprehension abilities, in the sense that there is an interaction between the development of prior knowledge in influencing the ability to create sentence structures and students' reading comprehension abilities.